Design and Development of a Wastewater Treatment Plant System for Improved Ammonia Removal at Metro Medika Hospital - Hairun Anwar; Taufik Abdullah; Azwaruddin Azwaruddin; Hismi Susane (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Hospital wastewater contains various pollutants, including ammonia, which may contaminate receiving water bodies and threaten environmental health if not adequately treated. The existing wastewater treatment plant (WWTP) at Metro Medika Hospital, Mataram, was unable to consistently reduce ammonia concentrations to comply with the regulatory limit of 10 mg/L, with the latest effluent concentration reaching 58.1 mg/L. Therefore, this study aimed to redesign the hospital WWTP to improve ammonia removal through the optimization of an integrated anaerobic-aerobic biological treatment system. A laboratory-scale experimental study was conducted using actual hospital wastewater in a modified treatment system consisting of anaerobic and aerobic biofilters, a bioball reactor, and a disinfection unit. The novelty of this study lies in integrating sequential anaerobic-aerobic biological treatment with a combination of attached-growth biofilter media, including DD-01 media, honeycomb media, bioballs, gravel, silica sand, zeolite, and plastic media, to enhance nitrification performance while maintaining a simple and practical treatment configuration. Data were analyzed using descriptive analysis by comparing influent and effluent ammonia concentrations, while treatment performance was evaluated through ammonia removal efficiency calculations. The redesigned WWTP reduced ammonia concentration from 58.1 mg/L to 10.0 mg/L, corresponding to an ammonia removal efficiency of 82.77%, thereby meeting the applicable wastewater quality standard. These findings demonstrate that the proposed WWTP design offers a feasible approach for improving ammonia removal and a promising strategy to support sustainable hospital wastewater management and regulatory compliance.